"Controlled competition": How governments can induce long-term competition - Yutaka Suzuki (Journal of Government and Economics (JGE), 2024)
This paper builds a model of dynamic tournaments under incomplete contract situations to analyze how the government, as a national development strategy, induces incentives or forms of competition between multiple companies (between state-owned enterprises (SOEs), between private-owned enterprises (POEs), or between SOEs and POEs) in the long-run. This paper can be considered as a model analysis of "controlled competition" under "State Capitalism", in which the government participates in the market as an active player, such as in China, Singapore, and in a broad sense, in Japanese Industrial Policy in the past. In addition to clarifying the incentive mechanism embedded in this model, we also examine the problems and areas for improvement from the perspective of incentive design. In particular, in the long-term competition between two heterogeneous companies, it would be a beneficial policy for the government if the feedback effect could be mitigated by handicapping the winner and favoring the loser, thereby restoring the competitive pressure that had decreased. At the same time, as excessive competition-inhibiting discriminatory prizes ("Cronyism") greatly impede investment incentives for both companies, these can be viewed as a "government failure", and thus the institution should be redesigned to correct such obstacles, thereby maintaining appropriate competitive pressures.
Keywords: D86; D23; O21; P11; 330; Controlled Competition; Cronyism; Dynamic Tournaments; Heterogeneity; Incomplete Contracts; State Capitalism